Runtime reduction in optimal multi-query sampling-based motion planning - Khaksar W.; Sahari K.S.B.M.; Ismail F.B.; Yousefi M.; Ali M.A. (Institute of Electrical and Electronics Engineers Inc., 2023)
Algorithms; Dispersions; Manufacture; Query processing; Robotics; High-dimensional; Low dispersions; Optimal solutions; Path length; Planning tasks; Sampling-based; Sampling-based algorithms; Sampling-based motion planning; Motion planning